2018
DOI: 10.18805/ijare.a-4923
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability and genetic advance studies in french bean (Phaseolus vulgaris L.) genotypes

Abstract: An experiment on evaluation in 36 genotypes of french bean was conducted at department of vegetable science, college of Horticulture, Bagalkot during rabi season of the year 2015-2016. The analysis of variance was significant (p=0.01) for all characters indicated higher magnitude of variability. Moderate GCV and PCV were observed for the traits plant height, number of primary branches, pod length, pod width, pod flesh thickness, number of pods / cluster, number of pods/ plant, weight of ten pods, number of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…Minimum dry matter content of 7.14% was found with variety V 3 (Arka Visthar). Similar variations for dry matter content in edible pods were reported by Jhanavi et al (2018).…”
Section: Quality Parameterssupporting
confidence: 87%
“…Minimum dry matter content of 7.14% was found with variety V 3 (Arka Visthar). Similar variations for dry matter content in edible pods were reported by Jhanavi et al (2018).…”
Section: Quality Parameterssupporting
confidence: 87%
“…The traits with high heritability viz., 10 pod weight (g), number of pods per cluster, number of seeds per pod can be improved by simple selection. Jhanavi et al (2018), Singh and Singh (2013), Ahmed and Kamaluddin (2013) reported high heritability for 10 pod weight (g), number of pods per cluster, pod length (cm), yield per plant, plant height (cm), number of primary branches per plant and number of pods per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, characters such as leaf area (32.84%), number of branches (39.02%), number of empty pods (26.23%), pod length (48.83%), and number of seeds per pod (45.40%) have moderate heritability values. Jhanavi et al (2018) reported a similar result, where the kidney beans tested had heritability values ranging from 63.32% to 85.36% and were classified as high. * statistically significant, in statitiscally insignificant, V e = environmental variation, V g = genetic variation, V p = phenotypic variation, h 2 bs = broad sense heritability, GCP = genetic coefficient of variation Some of the introduced kidney bean characters have a low genetic coefficient of variation values, such as seedling emergence (16.29%), plant height (19.56%), number of leaves (15.31%), number of branches (13.63%), stem diameter (13.97%), days to 50% flowering (10.42%), days to harvesting (3.37%), pod length (5.79%), and number of seeds per pod (9.73%).…”
Section: Variance Analysis Heritability and Genetic Coefficient Of Variationmentioning
confidence: 69%